Case report: Dueling etiologies: Longitudinally extensive spinal cord lesion mimicking spinal cord infarct with simultaneous positive Lyme serology and amphiphysin antibody - Kalaszi, Marianna; Donlon, Eoghan; Ahmad, Marzuki Wan; Mohamed, Abdirahman Sheikh; Boers, Peter (Frontiers in Neurology, 2022)
Background: Longitudinally extensive spinal cord lesions are challenging diagnostic entities as they are uncommon but various etiologies can cause them. Case Report: We report a case of a 55-year-old man with past medical history of hypertension, ex-smoker, presenting with chest pain, followed by right lower limb weakness, preceded by two weeks of constipation and voiding dysfunction. Examination revealed right lower limb mild flaccid paresis, absent reflexes, reduced anal tone and urinary retention. His symptoms deteriorated over 24 hours, he developed severe flaccid paraparesis with impaired pinprick sensation below T4 level. MRI spine showed abnormal, non-enhancing signal in the anterior aspect of the spinal cord extending from T4 level to the conus without associated oedema. He was commenced on intravenous steroids, with significant improvement after one dose. Imaging was felt to be consistent with spinal cord infarction and aspirin was started. Cerebrospinal fluid analysis showed elevated protein (0.80 mg/mL). Investigations for stroke and autoimmune pathologies were negative. Lyme Immunoblot confirmed intrathecal production of IgG to Borrelia antigens. The patient was started on ceftriaxone. Paraneoplastic screen identified amphiphysin antibodies. CT-TAP and PET-CT did not identify occult malignancy. The patient had significant improvement over two months, strength almost fully recovered, autonomic functions returned to normal. Conclusion: We describe an unusual, steroid-responsive longitudinally extensive spinal cord lesion with radiological features of spinal cord infarct and simultaneous finding of intrathecal Lyme antibodies and serum amphiphysin antibodies.